THE PHENOMENON OF COMPULSIVE BUYING BEHAVIOR DUE TO THE RISE OF FINTECH LENDING AMONG INDONESIAN MILLENNIALS - Yuwono, Wisnu; Juviyanty, Juviyanty; Nainggolan, Ferdinand (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Fintech lending is currently growing very rapidly, but has the potential for default by generation Z and millennials. This study aims to determine the effect of financial knowledge, financial attitude, financial management behavior, and self-control on compulsive buying behavior. This research is quantitative research, with a sampling technique using purposive sampling on the millennial generation who use fintech lending in Batam City, totaling 370 respondents. This study uses structural equation modeling (SEM) using SmartPLS software. The results of this study found that financial knowledge has an insignificant effect on compulsive buying behavior, while financial attitude and financial management behavior have a significant positive effect on compulsive buying behavior. Self-control is unable to significantly mediate the effect of financial knowledge on compulsive buying behavior, but self-control can significantly mediate the effect of financial attitude and financial management behavior on compulsive buying behavior. Based on the results of the research above, psychological problems such as stress, and anxiety as well as a high sense of prestige by spending excessive money will increasingly make people fall deeper into compulsive buying. The role of policymakers in regulating the use of FinTech lending and outreach to users through advertisements is suggested so that the public and fintech lending companies can get optimal benefits from using this technological advancement in the financial sector.